Evaluation of the bond strength of posterior composites to the dentin, treated with four different desensitizing agents - An In vitro study - C H Laxmi Priya; Savitha B Naik; N Kiran Kumar; Seema Merwade; Biji Brigit; Pavithra Prabakaran (Wolters Kluwer Medknow Publications, 2020)
Background: Postrestorative sensitivity is frequently associated with composite restorations. Dentin desensitizers are used commonly for the management of postrestorative sensitivity. This study aimed to evaluate the effect of four desensitizing agents on the bond strength of composite restoration. Materials and Methods: Sixty-five human premolars are used for the study. The occlusal surface of each tooth is flattened using a diamond disk to expose the dentin. The specimens are then etched with 35% phosphoric acid for 15 s and divided into five groups (n = 13) Group I - VivaSens, Group II - MS Coat F, Group III - Gluma, Group IV - Systemp, and Group V - Control. Single-step adhesive (Single Bond Universal, 3M) will be applied on the specimens and restored with composite material (Filtek Z350XT, 3 M). Shear bond strength is tested using universal testing machine at a crosshead speed of 1 mm/min. Statistically multiple group comparison was done using one-way analysis of variance followed by Tukey's test for group-wise comparison analysis. Results: Systemp desensitizer showed improved bond strength values than others desensitizers and control group. Conclusions: Systemp desensitizer can be considered as a promising option for preventing postoperative sensitivity associated with resin composite restorations without altering its shear bond strength to dentin.